Comparação do nível álgico no bloqueio do nervo alveolar inferior através de duas técnicas distintas - João Marcos Rodrigues de ARAGÃO; Klinger de Souza AMORIM; Rafael Soares da CUNHA; Francisco Carlos GROPPO; Liane Maciel de Almeida SOUZA
Abstract Introduction Blockade of the inferior alveolar nerve is among the most used and important anesthesia in dentistry, but there are no studies that compare the electronic anesthesia (Morpheus) and traditional manual anesthesia, using a syringe Carpule. Objective To evaluate and compare two anesthesia systems with respect to pain sensitivity during and after anesthesia with lidocaine 2% associated with epinephrine 1: 100,000 in anesthetic techniques for inferior alveolar nerve. Material and method This clinical trial was performed in a randomized, crossover, double-blind, involving 30 volunteers, who required dental treatment and who underwent blockade of the lower alveolar nerve, using the syringe type Carpule in the first session and the gun controlled speed Morpheus, where it was held in two sessions, with an interval of at least two weeks between each session. At the end of each session was applied to Visual Analogue Scale (VAS) to assess pain sensitivity to injection. Result A comparison between the conventional methods revealed that induce showed higher values than the EVA Morpheus. The chi -square for expected equal proportions showed that the technique with Morpheus had a higher (p = 0.0062) preference than conventional. Conclusion Taken together, the data show that the technique employing the Morpheus was superior to conventional in 3 times. The implementation of anesthesia performed with Morpheus proved to be more comfortable, have greater acceptance and preference for volunteers.